Evaluation of AA-CVD deposited phase pure polymorphs of SnS for thin films solar cells. Issue 26 (16th May 2019) - Ahmet, Ibbi Y.; Guc, Maxim; Sánchez, Yudania; Neuschitzer, Markus; Izquierdo-Roca, Victor; Saucedo, Edgardo; Johnson, Andrew L.
Abstract : Polymorph selective deposition of α- and π-SnS enables their evaluation as thin film PV absorber layers in various device structures. Abstract : Six different thin film solar cells consisting of either orthorhombic (α-SnS) or cubic (π-SnS) tin(ii ) sulfide absorber layers have been fabricated, characterized and evaluated. Absorber layers of either π-SnS or α-SnS were selectively deposited by temperature controlled Aerosol Assisted Chemical Vapor Deposition (AA-CVD) from a single source precursor. α-SnS and π-SnS layers were grown on molybdenum (Mo), Fluorine-doped Tin Oxide (FTO), and FTO coated with a thin amorphous-TiO x layer (am-TiO x -FTO), which were shown to have significant impact on the growth rate and morphology of the as deposited thin films. Phase pure α-SnS and π-SnS thin films were characterized by X-ray diffraction analysis (XRD) and Raman spectroscopy (514.5 nm). Furthermore, a series of PV devices with an active area of 0.1 cm 2 were subsequently fabricated using a CdS buffer layer, intrinsic ZnO (i-ZnO) as an insulator and Indium Tin Oxide (ITO) as a top contact. The highest solar conversion efficiency for the devices consisting of the α-SnS polymorph was achieved with Mo ( η = 0.82%) or FTO ( η = 0.88%) as the back contacts, with respective open-circuit voltages ( V oc ) of 0.135 and 0.144 V, and short-circuit current densities ( J sc ) of 12.96 and 12.78 mA cm −2 . For the devices containing the π-SnS polymorph, the highest efficiencies were obtained with the am-TiO x -FTO ( η = 0.41%) back contact, with a V oc of 0.135 V, and J sc of 5.40 mA cm −2 . We show that mild post-fabrication hot plate annealing can improve the J sc, but can in most cases compromise the V oc . The effect of sequential annealing was monitored by solar conversion efficiency and external quantum efficiency (EQE) measurements.